THE BEGINNING OF THE INTERNATIONAL HUMANITARIAN LAW APPLICATION TO CYBER ATTACK: THE STATUS OF RULE 30 TALLINN MANUAL 1.0 - Iradhati Zahra; Diajeng Wulan Christianti (Padjadjaran Journal of International Law, 2021)
ABSTRACTTechnological development has given rise to new means and methods of warfare such as cyber-attack and can potentially have devastating humanitarian consequences. In times of armed conflict, International Humanitarian Law (IHL) limits certain use of weapons, however, it is questionable whether an armed conflict exists in the situation where cyber-attack is employed alone. In 2007, Estonia suffered severe damages due to cyber-attacks that were equal to the damages caused by kinetic weapons. Yet, there is a debate whether IHL applies in the Estonia case due to the shortage of a kinetic weapon. The Estonia case has generated NATO and other states to draft a cyber-warfare manual (Tallinn Manual 1.0) that, in its Rule 30, affirms the IHL applicability in the case of only cyber-attack. Due to the importance of this Rule, this article argues that Rule 30 shall be considered as a legally binding provision in the form of customary international law. This Rule has satisfied widely practiced and opinio juris elements although it is not as ideal as other customary norms. Taking into consideration the rapid development of technology, it is not necessary for Rule 30 to meet the ideal condition of customary law since, according to Grotian Moment Theory, the formation of a new customary international law can be accelerated in times of fundamental change as can be seen in the practice of customary air and space law. Keywords: Customary International Law, Cyber-Attack, Grotian Moment Theory, IHL, Tallinn Manual 1.0 ABSTRAKPerkembangan teknologi telah melahirkan cara dan metode berperang yang baru seperti serangan siber dan dapat berpotensi menimbulkan kehancuran umat manusia. Hukum Humaniter Internasional (HHI) membatasi penggunaan senjata tertentu saat perang, sayangnya penerapan hukum ini masih dipertanyakan dalam kasus yang hanya melibatkan serangan siber. Tahun 2007 Estonia menderita kerugian akibat dari serangan siber yang tingkat keparahannya dapat disamakan dengan serangan kinetis. Namun, fakta bahwa serangan tersebut tidak melibatkan senjata kinetis melahirkan perdebatan perihal penerapan HHI. Kasus Estonia telah mendorong NATO dan negara-negara lainya untuk merumuskan Manual tentang Perang Siber (Tallinn Manual 1.0) yang mengkonfirmasi penerapan HHI untuk kasus yang hanya melibatkan serangan siber. Pentingnya pengaturan dalam Pasal 30, artikel ini berpendapat bahwa pasal tersebut harus memiliki kekuatan hukum yang mengikat dalam bentuk aturan hukum kebiasaan internasional. Pasal 30 telah memenuhi unsur hukum kebiasaan internasional yakni praktek negara yang luas serta opinio juris. Sekalipun tidak dipenuhi secara sempurna seperti layaknya aturan hukum kebiasaan internasional yang lain. Dengan mempertimbangkan perkembangan teknologi yang pesat, Pasal 30 tidak perlu secara ideal memenuhi unsur norma hukum kebiasaan internasional, karena menurut Grotian Moment Theory pembentukan norma hukum kebiasaan internasional baru dapat dipercepat karena adanya perubahan yang fundamental. Hal ini dapat terlihat dari praktek hukum kebiasaan ruang angkasa. Kata Kunci: Hukum Kebiasaan Internasional, Hukum Humaniter Internasional, Serangan Siber, Tallinn Manual 1.0, Teori Grotian Moment